Tyrosine phosphorylation of Munc18‐1 inhibits synaptic transmission by preventing SNARE assembly - Meijer, Marieke; Dörr, Bernhard; Söllner, Thomas (The EMBO journal, 2018)
Tyrosine kinases are important regulators of synaptic strength. Here, we describe a key component of the synaptic vesicle release machinery, Munc18‐1, as a phosphorylation target for neuronal Src family kinases (SFKs). Phosphomimetic Y473D mutation of a SFK phosphorylation site previously identified by brain phospho‐proteomics abolished the stimulatory effect of Munc18‐1 on SNARE complex formation (“SNARE‐templating”) and membrane fusion in vitro. Furthermore, priming but not docking of synaptic vesicles was disrupted in hippocampal munc18‐1‐null neurons expressing Munc18‐1Y473D. Synaptic transmission was temporarily restored by high‐frequency stimulation, as well as by a Munc18‐1 mutation that results in helix 12 extension, a critical conformational step in vesicle priming. On the other hand, expression of non‐phosphorylatable Munc18‐1 supported normal synaptic transmission. We propose that SFK‐dependent Munc18‐1 phosphorylation may constitute a potent, previously unknown mechanism to shut down synaptic transmission, via direct occlusion of a Synaptobrevin/VAMP2 binding groove and subsequent hindrance of conformational changes in domain 3a responsible for vesicle priming. This would strongly interfere with the essential post‐docking SNARE‐templating role of Munc18‐1, resulting in a largely abolished pool of releasable synaptic vesicles. - Synopsis - - - - This study identifies a novel regulatory site on the presynaptic protein Munc18‐1, which phosphorylated state prevents Synaptobrevin2/VAMP2 binding, SNARE‐templating and synaptic vesicle priming. Tyrosine phosphorylation of Munc18‐1 is a potent way to shut down synaptic transmission. - - Y473 on Munc18‐1 is a substrate for several neuronal members of Src family kinase.A single point mutation (Y473D) designed to mimic tyrosine phosphorylation interfered with Synaptobrevin2/VAMP2 binding and the stimulatory effect of Munc18‐1 on SNARE‐complex formation.Hippocampal munc18‐1 null neurons expressing Munc18‐1Y473D are defective in synaptic vesicle priming, but not docking.Synaptic transmission was largely restored by high frequency stimulation or by promoting helix 12 extension in domain 3a of Munc18‐1.